AIDS and COVID: A tale of two pandemics and the role of statisticians. (8th May 2021) - Ellenberg, Susan S.; Morris, Jeffrey S.
Abstract : The world has experienced three global pandemics over the last half‐century: HIV/AIDS, H1N1, and COVID‐19. HIV/AIDS and COVID‐19 are still with us and have wrought extensive havoc worldwide. There are many differences between these two infections and their global impacts, but one thing they have in common is the mobilization of scientific resources to both understand the infection and develop ways to combat it. As was the case with HIV, statisticians have been in the forefront of scientists working to understand transmission dynamics and the natural history of infection, determine prognostic factors for severe disease, and develop optimal study designs to assess therapeutics and vaccines.